DAMPAK INVESTASI ASING DAN DALAM NEGERI TERHADAP EKSPANSI EKONOMI DI KALIMANTAN TIMUR - Irawan Irawan; Puput Iswandyah Raysharie, Ahmad Ibra, Christop Dwi Putra, Elsa Margareta Julianti, Endrico Natanael (BORJUIS: JURNAL OF ECONOMY, 2024)
By using literature methods that focus on studying the influence of Indonesian economic expansion, PMA and PMDN. Data used is 2022 data sourced by the official website of the East Kalimantan Provincial Government and Niaga Asia (leading business and economic media). The findings of this inquiry reveal that foreign capital infusion exerts a favorable sway on the expansion of the economy, albeit lacking statistical significance. Conversely, the infusion of domestic resources bears substantial weight on the nation's economic advancement.